Simple Interest in a Reorganization Bankruptcy after the Supreme Court Resolution of 20th February 2013 (III CZP 96/12) - Witosz , Aleksander Jerzy (Studia Oeconomica Posnaniensia, 2015)
The case of simple interest in a reorganization bankruptcy is a controversial topic after the 2009 amendment to the Bankruptcy and Rehabilitation Law. Repealing the problematic Article 272 section 2 not only did not contribute to clarifying existing doubts, but also even brought about new problems. As a result of this regulatory change, statutes that concern reorganization bankruptcy were deprived of a clear standard to regulate the legal basis of simple interest after the date of insolvency. Consequently, an ongoing dispute has arisen as a result of this loophole, and the decision of 20th February 2013 (III CZP 96/12) is the Supreme Court's contribution to this issue